Institutional Transformation from Myth to Modern Action: Collaborative Efforts in Preserving Lengkong Lake, Indonesia - Wargadinata, Ella Lesmanawaty (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2024)
Irrational beliefs such as myths, legends, and taboos play a role in protected area conservation or biodiversity; however, those remain unanswered in their conceptualization and practices. This research aims to reveal how a myth as an ancient institution evolves into a modern institution accepted by today's generation. It uses institutional transformation as an essential guide to reveal the linear transformation from old legend as a traditional institution into a modern multi-actor collaboration—data collection through observation, interviews with purposive informants, and support by secondary data. The result shows that the current Lake conservation covers long run long-institutional evolution: from the legend of the Zamzam water as the starting point, the legalization of the site as a natural conservation area, the strong kinship bond among local peoples, the metamorphosis of myth into public cultural events; to modern Collaborative action on religious tourism management of who, what, and when benefit and responsibility from different actors are shared. The institutional transformation has become a focal point over modernization that is intertwined and plays a significant role in the Lengkong Lake conservation.